The arrangement of on-line training of master students, majoring in Mathematics for internship in technical universities - Vlasenko, Kateryna; Lovianova, Iryna; Chumak, Olena; Achkan, Vitaliy; Sitak, Irina (IOP Publishing, 2021)
This article looks into the issue of online-training of master students, majoring in Mathematics for internship in technical universities. This study is focused on arranging students' learning activities with the help of an on-line course “Methods for teaching Mathematics to students in technical universities”. The study considers the issues that students face during the internship in technical universities and debates a possibility to factor in the students’ needs while designing the course content.